Cross-sectional investigation of indices of isokinetic leg strength in youth soccer players and untrained individuals - Iga, J.; George, K.; Lees, A.; Reilly, T. (Scandinavian Journal of Medicine & Science in Sports, 2009)
In this cross-sectional study, the differences in the isokinetic peak torque of the knee joint muscles (dominant and non-dominant) were investigated in three groups of youths (n=45; age, 14.9±1.1 years) with different soccer training backgrounds. Significant main effects were observed for training background on the functional hamstrings to quadriceps ratios for knee flexion (HCON:QECC ratio; F2,42=4.023, P=0.025) and extension (HECC:QCON ratio; F2,42=8.53, P<0.001) at 4.32 rad/s. Post hoc tests indicated that both ratios were significantly different between conventionally trained players compared with resistance-trained players and controls (mean±SD; HECC:QCON ratio, dominant limb; 0.91±0.10; 1.04±0.12; 1.10±0.22; non-dominant limb; 0.89±0.09; 1.05±0.19; 1.06±0.15; HCON:QECC ratio, dominant limb; 0.36±0.06; 0.34±0.07; 0.30±0.08; non-dominant limb; 0.33±0.05; 0.32±0.08; 0.28±0.07). Results suggest that the muscle-loading patterns experienced in youth soccer may alter the reciprocal balance of strength about the knee under high-velocity conditions. The findings also indicate that these balances may be improved by incorporating resistance training into the habitual exercise routines of youth soccer players.